Revisiting the taxonomy of Korean Ischnochiton species (Polyplacophora, Ischnochitonidae) based on a combined analysis of morphological and molecular data - Park, Jina; Kim, Yukyung; Putri, Eggy Triana; Park, Joong-Ki (Pensoft Publishers, 2024)
Chiton species belonging to the genus Ischnochiton J. E. Gray, 1847 are commonly found in intertidal rocky shores worldwide, with the exception of the northern Atlantic and Arctic oceans. Ischnochiton species are characterised by imbricate girdle scales that are uniform in size, rounded, sculpted with striae or occasionally smooth. However, their species-level taxonomy is complicated due to the high variation in their shell microstructures. Despite more than a hundred species reported worldwide, taxonomic studies of this group remain relatively unexplored in Korean waters, with only a few species recorded to date. In this study, we compared the microstructural characteristics of tegmentum sculpture, girdle scales and radula amongst four Korean Ischnochiton species using high-resolution microscopic images and a scanning electron microscope (SEM). Along with mtDNA cox1 sequence comparison, a comprehensive analysis of their morphology revealed that I. hayamii Owada, 2018 was identified for the first time in Korean waters. This species is morphologically distinguished by its small body size of adults, smooth lateral areas on valves and small perinotum scales sculptured with weak longitudinal ribs. Phylogenetic analysis of the mtDNA cox1 sequence provides distinct resolution at the species level, but interrelationships amongst Ischnochiton species remain unresolved. Results from the morphological and molecular analyses presented in this study offer valuable taxonomic information for accurate species identification amongst closely-related Ischnochiton species.